5. INOVASI MANAJEMEN PEMERINTAHAN DAERAH DALAM PENANGGULANGAN KEMISKINAN DI KOTA PEKALONGAN - Kushandajani Kushandajani (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
This research is motivated by the deepen concern toward  the fenomena of poverty in Indonesia, in otherhand application of decentralization is exist for a while. So, it’s important thing to study how to make poverty reduction with innovation programes in decentralization era. Result this research describes that the capasity of Walikota to puss four social institutions: Badan Keswadayaan Masyarakat (BKM), Lembaga Pemberdayaan Masyarakat (LPM), Pendidikan Kesejahteraan Keluarga (PKK), and Karang Taruna can solve the poverty problems in Kota Pekalongan. There are many innovation programes in Kota Pekalongan, where All programes are community based: Replication of Program Penangggulangan Kemiskinan Perkotaan (P2KP), Program Percepatan Pembangunan Keluarga Sejahtera Berbasis Masyarakat (P2KSBM), Program Daerah Pemberdayaan Masyarakat (PDPM), and Replication of Pembangunan Lingkungan Permukiman Berbasis Komunitas (PLPBK) that focused in neighborhood develompent.By means of strengtening capacityof social institution at Kelurahan also integrated planning and budgeting, innovation programs can be done succesfully.